2015
DOI: 10.1097/pas.0000000000000366
|View full text |Cite
|
Sign up to set email alerts
|

Myogenic Differentiation and Histologic Grading Are Major Prognostic Determinants in Retroperitoneal Liposarcoma

Abstract: The aim of the present work was to improve the understanding of the impact of malignancy grade and myogenic/rhabdomyoblastic differentiation on the natural course of retroperitoneal liposarcoma. All consecutive patients affected by primary well-differentiated (WD)/dedifferentiated (DD) retroperitoneal liposarcoma, surgically treated at our institution between January 2002 and December 2011, were retrospectively evaluated. Tumors were stained for mdm2 and 5 myogenic markers (smooth muscle actin-α, h-caldesmon, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 33 publications
4
91
2
3
Order By: Relevance
“…However, the follow‐up periods of this study might not be long enough to assess true life outcomes. High histological grade and a retroperitoneal tumour location have been reported repeatedly to be associated with worse outcomes in DDLPS . In our study, histological grade was the most important prognostic factor, while retroperitoneal tumour location was related only to shorter LRFS.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, the follow‐up periods of this study might not be long enough to assess true life outcomes. High histological grade and a retroperitoneal tumour location have been reported repeatedly to be associated with worse outcomes in DDLPS . In our study, histological grade was the most important prognostic factor, while retroperitoneal tumour location was related only to shorter LRFS.…”
Section: Discussionsupporting
confidence: 57%
“…It is also widely recognised that DDLPS sometimes exhibits heterologous differentiation . Myogenic differentiation is the most common type, and the impact of myogenic differentiation on prognosis has been investigated . Conversely, formation of bone tissue has been reported in 0.6–29% of cases in large studies of DDLPS, and the bone formation has usually been described as either ‘osteosarcomatous differentiation’ or ‘metaplastic bone formation’ according to histological analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Low-grade tumors carry the risk of local recurrence, but rarely cause distant metastases. 12,13 The objective of this review is to evaluate the most important…”
Section: Introductionmentioning
confidence: 99%
“…Although somewhat limited in number, our cases followed a typical disease course for WDLPS / ALT, characterized by local recurrence in 2/7 cases (28.5%). Of note, Gronchi et al recently found that myogenic differentiation was associated with a poor prognosis in retroperitoneal liposarcoma 28 . However this study examined both well-differentiated and dedifferentiated tumors, and included both markers of smooth and skeletal muscle differentiation.…”
Section: Discussionmentioning
confidence: 98%